Educação Infantil: apontamentos da prática de uma auxiliar na creche - Rosa, Tatiane Tomazini Soares (Universidade Federal de São Carlos, 2023)
This work is a reflection of the daily work of an education assistant from questions about the division of labor in early childhood education. The objective was to analyze the role of the early childhood education assistant working in the daycare center, its most diverse nomenclatures, work structures and other factors that lead to its precariousness and devaluation. A survey of the historical context of Brazilian early childhood education and especially of the emergence of early childhood education in the city of Sorocaba, SP, was elaborated. We made a historical and legislative survey about the creation of the position of the auxiliary sorocabana. And from this and the theory of the professor-researcher based on Lawrence Stenhouse, a reflection was made from the reality of the daily life experienced on the organization of work and the academic training of the assistant.
Child education: notes from the practice of a daycare assistant
Keywords: auxiliar de educação; creche; Educação infantil; trabalho docente; Education Assistant; Children's daycare; Child Education; Teacher work; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO